Microstructural and mechanical properties of SiO₂-Na₂O-CaO-P₂O₅-CaF₂ Bioglass/Hydroxyapatite composite - Adnin, Noorfauzana (2018)
In spite of tremendous applications of bioactive glasses, their low mechanical properties such as low strength and high brittleness have limited their clinical applications as load-bearing implants. To overcome these limitation hence in this study, an alternative approaches proposed is by the development a novel composite of Bioglass (BG) and Hydroxyapatite (HA) via thermal treatment method. However, under such sintering conditions, the poor thermal stability of HA (dehydration and decomposition process) which occurred remarkably should be taken into account, since it declines the mechanical properties of the composite. Therefore, Calcium Fluoride (CaF2) was incorporate into BG composition to improve the thermal stability of HA. In this research work, the purpose is to investigate the microstructure and mechanical properties and also their relationship of new BG-HA biocomposite with the incorporation of CaF2 in BG system. Such observation is not documented in the literature in this scope of research since investigations on the microstructure, mechanical properties and also their relationship of based BG have remained pointing only towards the effect of heat treatment and liquid phase sintering (LPS), without considering the role of CaF2 on the microstructure and mechanical properties of BG-HA composite. In addition, in this study, the observation of parallel relation of microstructure and mechanical properties of the BG-HA composites at each stages of sintering temperature was also elucidated. SiO2-Na2O-CaO-P2O5-CaF2 were prepared by conventional melt quenching method and were mixed with HA through solid state reaction, in proportion of 0, 10, 20, 30 and 40 wt% respectively. Each composition was sintered from 500 to 1000 °C with 50 °C increments. The samples were characterized by Thermal Gravimetric Analysis-Differential Scanning Calorimetry (TGA-DSC), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Field Effect Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy (FESEM-EDAX), density, grain size, microhardness and compressive strength measurement. FTIR analysis showed the evidence of non-bridging oxygens (NBO’s) with the increase of the network-modifying species content (CaF2), which responsible for the decrease in the volume of network structure thus increase the value of density. The XRD analysis indicated that BG with 10 wt% HA content sintered at 800 °C show high thermal stability by the presence of Na2Ca3 Si2O8, Na4CaSi3O9, Na2Ca3Si6O16, HA, FA and with the absence of β-TCP phases. FESEM micrograph illustrated increasing of grain size by the increasing of sintering temperature. The result shows that density, hardness and compressive strength improved from 500-800 °C sintering temperature. However, at 850-1000 °C sintering temperature the density, hardness and compressive strength significantly decreased. Finally, density of 2.95 g/cm3, hardness of 250 HV and compressive strength value of 103 MPa has been attained for BG with 10 wt% HA content sintered at 800 °C. The superior mechanical strength was attributed to the improved densification by heat treatment, LPS and also by the improvement of HA thermal stability through the incorporation of CaF2.